Atomic tuning effect of TiB2 particles on the liquid phase separation behavior of an Al-Bi immiscible alloy. (1st March 2022) - Cao, Saichao; Lu, Wenquan; Hu, Qiaodan; Yu, Pengfei; Ge, Xuan; Lai, Pingsheng; Li, Jianguo
Abstract: Microparticles are usually applied to obtain homogenous microstructure in immiscible alloys, but their role on the atomic-scale structural evolution during the liquid-liquid separation process has not been fully understood. Here we employed in situ high-energy X-ray diffraction (HE-XRD) combined with Reverse Monte Carlo calculations (RMC) to investigate the melt structure of an Al-60 wt.%Bi immiscible alloy with and without TiB2 particles. The results show that liquid separation can be mainly characterized by the changes in atomic spacing of Bi, and the first shell layer of Bi droplets is in crystal order in the Al-Bi melt. Addition of TiB2 particles changes the first shell layer of Bi droplets to a disorder structure, and consequently reduces the temperature for liquid separation. These findings break the conventional cognition that microparticles can promote nucleation of minor droplets, and provide a new perspective of the inhibiting effect of microparticles in immiscible alloys. Graphical abstract: Image, graphical abstract